Aproximación a la evolución reciente de la gran propiedad agrícola en el Bajo Segura: el caso de Orihuela - Canales Martínez, Gregorio; Crespo Rodríguez, Fermín (Investigaciones Geográficas, 1987)
The municipality of Orihuela has a huge extension of land, most of it unirrigated. This is the reason why the study analyses the recent evolution of these large properties from the decade of the forties onwards. These country estates of the Bajo Segura have experimented in the last decades changes of great significance, on one hand, the dry lands have been transformed into irrigated ones with the waters of the Trasvase Tajo-Segura; on the other hand, and due to the fact that they are close to the coast, some of them are now turistic urbanizations. Therefore, we now find a speculative use of the land based on a fertile agriculture and on a turistic development. One use does not exclude the other and in some properties both of them are combined.